Dysregulation of multiple signaling pathways: A possible cause of cerebral palsy. Issue 9 (May 2022) - Upadhyay, Jyoti; Ansari, Mohd Nazam; Samad, Abdul; Sayana, Ashutosh
Cerebral palsy (CP) is a lifelong disability characterized by the impairment of brain functions that result in improper posture and abnormal motor patterns. Understanding this brain abnormality and the role of genetic, epigenetic, and non-genetic factors such as signaling pathway dysregulation and cytokine dysregulation in the pathogenesis of CP is a complex process. Hypoxic–ischemic injury and prematurity are two well-known contributors of CP. Like in the case of other neurodevelopmental disorders such as intellectual disability and autism, the genomic constituents in CP are highly complex. The neuroinflammation that is triggered by maternal cytokine response plays a critical role in the pathogenesis of fetal inflammation response, which is one of the contributing factors of CP, and it continues even after the birth of children suffering from CP. Canonical Wnt signaling pathway is important for the development of mammalian fetal brain and it regulates distinct processes including neurogenesis. The glycogen synthase kinase-3 (GSK-3) antagonistic activity in the Wnt signaling pathway plays a crucial role in neurogenesis and neural development. In this review, we investigated several genetic and non-genetic pathways that are involved in the pathogenesis of CP and their regulation, impairment, and implications for causing CP during embryonic growth and developmental period. Investigating the role of these pathways help to develop novel therapeutic interventions and biomarkers for early diagnosis and treatment. This review also helps us to comprehend the mechanical approach of various signaling pathways, as well as their consequences and relevance in the understanding of CP.